Microencapsulation of ciplukan (Physalis angulata L.) extract as food ingredients: Effect of water ratio and maltodextrin concentration variables on product characteristics - Iwansyah, Ade Chandra; Wardhani, Riuh; Darsih, Cici; Kurniawan, Taufik; Ariani, Dini; Andriana, Yusuf; Karim, Mirwan Ardiansyah; Indriati, Ashri; Luthfiyanti, Rohmah; Hazrulrizawati, Abd Hamid (Universiti Putra Malaysia, 2023)
The present work evaluated the characteristics of ciplukan (Physalis angulata L.) microcapsule extracts prepared by spray drying method. Different water ratios namely X1 (1:2), X2 (1:5), and X3 (1:10), and maltodextrin concentrations namely Y1 (5%) and Y2 (10%) were applied in a spray drying system to produce microcapsule extracts. Investigations of physical properties (pH, moisture, water activity, total solid, solubility, and colour), as well as morphological characteristics by scanning electron microscopy (SEM) and functional properties (antioxidant, total phenolic, total flavonoid, and quercetin content) were carried out. Results showed that water ratio and maltodextrin gave a significant effect on the physical properties of microcapsule extract with X1 (1:2) and Y1 (5 %) having significant effect on total phenolic, flavonoid, and quercetin contents, and antioxidant properties of ciplukan extract microcapsule. Furthermore, the scanning electron microscopy (SEM) illustrated the morphological structure of microcapsule extract, which showed a spherical structure. All combinations of water ratios and maltodextrin concentrations showed agglomeration, except for X1Y2. In correlation analysis using partial least square, the antioxidant activity of microcapsule extract was proportional to physicochemical properties, total phenolic, total flavonoid, and quercetin contents of microcapsule extract. The present work revealed that water extraction ratios and maltodextrin concentrations affected microcapsule extract of ciplukan. The combination of X1 (1:2) and Y1 (5%) retained the functional properties of ciplukan microcapsule extract.